2016
DOI: 10.1002/jqs.2836
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐Pleistocene thin‐skinned glaciotectonic thrusting of the Aberdeen Ground Formation, Central Graben region, central North Sea

Abstract: This paper presents the results of a high-resolution 2D seismic survey of Mid-Pleistocene glaciogenic sediments in the Central Graben region of the central North Sea. The survey has revealed that these sediments, which were originally interpreted as possessing a simple layercake stratigraphy, have in fact undergone major glaciotectonic thrusting and folding associated with the repeated southerly advance of an ice sheet across the region during the Mid-Pleistocene. The total observed length of the thrust-stacke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…The recognition of a buried glacial landscape within the DBF (Figure 1(b) and (c)), coupled with the detailed analysis of seismic profiles in three key areas (Figures 2-5), have revealed that the Dogger Bank is, at least in part, composed of a complex moraine system comprising variably deformed (folded and thrusted) sediments. Comparable large-scale glaciotectonic complexes comprising folded and thrusted glaciogenic sediments have been described elsewhere within the North Sea Basin and adjacent areas (e.g., Andersen et al 2005;Phillips et al 2008;Burke et al 2009;Bakker and van der Meer 2003;Vaughan-Hirsch and Phillips 2017;Lee et al 2013Lee et al , 2017Pedersen and Boldreel 2017). The complexity of the structural and sedimentary architecture of the DBF within the foundation zone of the proposed offshore wind farm has profound implications for the siting and design of the turbine foundations.…”
Section: Discussionmentioning
confidence: 67%
“…The recognition of a buried glacial landscape within the DBF (Figure 1(b) and (c)), coupled with the detailed analysis of seismic profiles in three key areas (Figures 2-5), have revealed that the Dogger Bank is, at least in part, composed of a complex moraine system comprising variably deformed (folded and thrusted) sediments. Comparable large-scale glaciotectonic complexes comprising folded and thrusted glaciogenic sediments have been described elsewhere within the North Sea Basin and adjacent areas (e.g., Andersen et al 2005;Phillips et al 2008;Burke et al 2009;Bakker and van der Meer 2003;Vaughan-Hirsch and Phillips 2017;Lee et al 2013Lee et al , 2017Pedersen and Boldreel 2017). The complexity of the structural and sedimentary architecture of the DBF within the foundation zone of the proposed offshore wind farm has profound implications for the siting and design of the turbine foundations.…”
Section: Discussionmentioning
confidence: 67%
“…They are characterized by an asymmetric mean longitudinal profile with a distal slope that is exceeding the proximal. However, composite ridges can be interpreted as surface expressions of fault-related folds, which show asymmetric profiles in relation to push direction, similar to push moraines [3,4,24]. An analysis of a glacitectonic environment, like Jasmund, needs to deal with this complication.…”
Section: Geosciences 2018 8 X For Peer Review 2 Of 24mentioning
confidence: 99%
“…Pushing and thrusting of the advancing ice front, regardless of whether push moraines or composite ridges are formed, would very likely result in asymmetric cross profiles, usually with steeper distal and flatter proximal slopes (e.g., [4,13,32]). Thus, the flow-parallel topographic profile seems to be rather a weak tool to distinguish between the two landforms.…”
Section: Terminology Of the Surface Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The glacitectonic theme is continued in the paper by Vaughan-Hirsch and Phillips (2017). This paper presents the results of a high-resolution 2D seismic survey of mid-Pleistocene glaciogenic sediments in the Central Graben region of the central North Sea (10 on Fig.…”
Section: Contents Of the Special Issuementioning
confidence: 99%